Biochemical assessment of metabolic associated fatty liver disease - Guerra-Ruiz Armando R.; Casals Gregori; Iruzubieta Paula; Lalana Marta; Leis Alba; López Rosa María; Crespo Javier; Morales-Ruiz Manuel (Advances in Laboratory Medicine, 2021)
Metabolic-associated fatty liver disease (MAFLD) is defined as fat accumulation in the liver in the presence of metabolic alterations. This disorder is generally asymptomatic and may progress to severe liver disease, which are linked to inflammation and/or fibrosis. MAFLD has a high prevalence (26%) and therefore a considerable number of patients are at high risk of having advanced liver disease. This document provides an overview of the most relevant serological markers in the characterization and diagnosis of MAFLD. An example is provided of a routine diagnostic algorithm that incorporates serological testing. A range of useful serological scores are currently available for the management of MAFLD patients, especially for the stratification of patients at risk of fibrosis. A large proportion of the population is at risk of developing severe liver disease. The integration of non-invasive serological markers in the stratification of patients at risk for liver fibrosis may contribute to improve the control and management of MAFLD patients.